An Overview of Biogas Production: Fundamentals, Applications and Future Research - Sawyerr, Nathaniel; Trois, Cristina; Workneh, Tilahun; Okudoh, Vincent (International Journal of Energy Economics and Policy, 2019)
Due to the increase in population, both developed and developing countries are facing mainly issues surrounding the future energy security and a better use of natural resources. Such present and future energy problems can be solved by the use of renewable energy sources. Among several renewable energy sources is a sustainable means of anaerobic digestion for production of gases. In the past, anaerobic digestion as a source of biogas was used mainly for degradation of waste materials or toxic compounds. However, recently, there has been great interest in producing biogas from energy crops. This paper presents an overview of state-of-the-art and future viewpoints related to the anaerobic digestion process for biogas production. Keywords: Biogas, Biomass, Anaerobic Digestion, Methane, Renewable Energy JEL Classifications: Q4, P28 DOI: https://doi.org/10.32479/ijeep.7375